ANALISIS FAKTOR-FAKTOR YANG MEMEGARUHI PRODUKSI PADI SAWAH DI DESA UETOLI KECAMATAN AMPANA TETE KABUPATEN TOJO UNA-UNA - Tri Ifgayani; I Made Antara; Lien Damayanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
This study aimed to analyze factors affecting lowland rice production in Uetoli village of Ampana Tete sub-district. This village is one of the centers of rice production in Tojo Una-Una district. Population of this study was lowland rice farmers in Uetoli village within which 34 respondents were selected.  Data collected was analyzed using the Cobb-Douglas production function analysis. The results of the study indicated that those variables such as land area (X1), number of seeds (X2), urea fertilizer (X3), phonska fertilizer (X4), and labor (X5) were simultaneously affected the rice production with F-counted value was 58.53 larger than the F-table (3.76) at 1% significance level (α) and R2 value was 0.955 indicating that 95.5% of variation in the rice production (Y) can be described by these variables. The coefficient regression was 0.429 for the land area (X1), 0.217 for the number of seeds (X2), 0.169 for the amount of urea fertilizer (X3), 0.163 for phonska fertilizer (X4), and 0.155 for the labor (X5). Keywords : Cobb-Douglas Production Function, Lowland Rice, and Regression.